The Impact of Midwifery-Led Care on Birth Outcomes in Low-Risk Pregnancies - Ernawati, Ernawati (Advances in Healthcare Research, 2024)
Purpose: This study aims to investigate the impact of midwifery-led care on birth outcomes in low-risk pregnancies. Research Design and Methodology: Grounded in a comprehensive literature review, this study employs a qualitative research approach to synthesize existing knowledge on midwifery-led care. A systematic search and analysis of peer-reviewed articles, clinical reports, and grey literature were conducted to explore the efficacy of midwifery-led care compared to conventional medical care. Findings and Discussion: The findings highlight the significant reduction in medical interventions associated with midwifery-led care, the promotion of physiological childbirth, and enhanced maternal and neonatal well-being. Key factors, including continuity of care, patient-provider relationships, and cultural competence, are crucial in optimizing outcomes. Implications: Policy implications include integrating midwifery care into mainstream healthcare systems, investing in midwifery education, and advocating for legislative support to ensure equitable access to high-quality maternity care.